2021
DOI: 10.3390/ijerph18083972
|View full text |Cite
|
Sign up to set email alerts
|

Callous–Unemotional Traits among Adolescents with Autism Spectrum Disorder, Attention-Deficit/Hyperactivity Disorder, or Typical Development: Differences between Adolescents’ and Parents’ Views

Abstract: This study examined parent–adolescent agreement on the callous, uncaring, and unemotional dimensions of callous–unemotional (CU) traits and the differences in adolescent-reported and parent-reported CU traits among 126 adolescents with autism spectrum disorder (ASD), 207 adolescents with attention-deficit/hyperactivity disorder (ADHD), and 203 typically developing (TD) adolescents. Adolescent-reported and parent-reported CU traits on the three dimensions of the Inventory of Callous and Unemotional Traits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…As mentioned before, probably the level of severity (Enea & Rusu, 2020) is the factor that may be related to difficulties and may interact with CU traits in creating a "double-hit". It has been observed that individuals with autistic traits can also display higher levels of CU traits (Chang et al, 2021;Leno et al, 2015;Rogers et al, 2006). However, this association is linked to less severe antisocial behavior.…”
Section: Unique Associations and Interaction Effectsmentioning
confidence: 99%
“…As mentioned before, probably the level of severity (Enea & Rusu, 2020) is the factor that may be related to difficulties and may interact with CU traits in creating a "double-hit". It has been observed that individuals with autistic traits can also display higher levels of CU traits (Chang et al, 2021;Leno et al, 2015;Rogers et al, 2006). However, this association is linked to less severe antisocial behavior.…”
Section: Unique Associations and Interaction Effectsmentioning
confidence: 99%
“…CU traits are a correlate of ODD, often a core feature of CD, and a key etiologic and phenotypic modi er of conduct problems (Frick et al, 2014). Second, ADHD is associated with elevated CU traits in children with ADHD and ODD not meeting criteria for CD [9,10] and in children with ADHD, elevated CU traits increases the probability of developing ASPD, independent of comorbid CD [11].…”
Section: Introductionmentioning
confidence: 99%